2015
DOI: 10.1038/cddis.2015.239
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-26a supports mammalian axon regeneration in vivo by suppressing GSK3β expression

Abstract: MicroRNAs are emerging to be important epigenetic factors that control axon regeneration. Here, we report that microRNA-26a (miR-26a) is a physiological regulator of mammalian axon regeneration in vivo. We demonstrated that endogenous miR-26a acted to target specifically glycogen synthase kinase 3β (GSK3β) in adult mouse sensory neurons in vitro and in vivo. Inhibition of endogenous miR-26a in sensory neurons impaired axon regeneration in vitro and in vivo. Moreover, the regulatory effect of miR-26a was mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 27 publications
3
61
0
Order By: Relevance
“…The evidence suggested that miR-26a-5p activity may have a compartmentalized response which would operate differently for the outgrowth of dendrites and axons. For instance, increased miR-26a-5p enhanced axon outgrowth in hippocampal neurons and axon regeneration in the peripheral nervous system [44], [62]. Interestingly, this dual cell response is also observed after decreasing GSK3 (a validated miR-26a-5p target) activity in hippocampal neurons [63].…”
Section: A Role For Sevs In Tranferring Glial Mirnas To Neurons and Tmentioning
confidence: 96%
See 1 more Smart Citation
“…The evidence suggested that miR-26a-5p activity may have a compartmentalized response which would operate differently for the outgrowth of dendrites and axons. For instance, increased miR-26a-5p enhanced axon outgrowth in hippocampal neurons and axon regeneration in the peripheral nervous system [44], [62]. Interestingly, this dual cell response is also observed after decreasing GSK3 (a validated miR-26a-5p target) activity in hippocampal neurons [63].…”
Section: A Role For Sevs In Tranferring Glial Mirnas To Neurons and Tmentioning
confidence: 96%
“…To validate miR-26a-5p activity in the regulation of neuronal morphology, we analyzed the protein levels of its validated target gene products Microtubule Associated Protein 2 (MAP2) [43] and Glycogen Synthase Kinase 3  (GSK3) [44], which also play a key function in neuronal morphology [45], [46]. For this, we evaluated by Western blot the protein levels of MAP2 and GSK3 in hippocampal neurons magnetofected either with a scrambled control nucleotide sequence, a nucleotide sequence that mimics endogenous miRNA-26a-5p (mimic 26a-5p) or an inhibitor nucleotide sequence targeting miRNA-26a-5p (antago 26a-5p) for 72 hours.…”
Section: Astrocyte-derived Sevs Carry Mir-26-5p Which Targets Gene Ementioning
confidence: 99%
“…The expression of GSK3β can be decreased via expression of miR-26a, leading to promotion of neuronal axon regeneration through gene regulation (Jiang et al, 2015). By inhibiting the proliferation of axons, miR-26 represents a case of gene regulation leading to accelerated aging.…”
Section: Mirna Synthesis/actionmentioning
confidence: 99%
“…In our recently published research, we found that miR-26a promotes axon regeneration by suppressing GSK3 β expression in mammals [92]. In retinal ganglion cells, miR-30b has been proved to promote axon outgrowth by inhibiting the expression of semaphorin 3A (Sema3A), which is a major inhibitory factor of optic nerve (ON) regeneration after injury [93].…”
Section: Micrornas and Intrinsic Determinants Of Axon Regenerationmentioning
confidence: 99%